Direct versus indirect realism : a neurophilosophical debate on consciousness - Smythies, John R. (John Raymond), 1922-; French, Robert E., 1952- (Academic Press, 2018)
Direct versus Indirect Realism: A Neurophilosophical Debate on Consciousness brings together leading neuroscientists and philosophers to explain and defend their theories on consciousness. The book offers a one-of-a-kind look at the radically opposing theories concerning the nature of the objects of immediate perception-whether these are distal physical objects or phenomenal experiences in the conscious mind. Each side-neuroscientists and philosophers-offers accessible, comprehensive explanations of their points-of-view, with each side also providing a response to the other that offers a unique approach on opposing positions. It is the only book available that combines thorough discussion of the arguments behind both direct and indirect realism in a single resource, and is required reading for neuroscientists, neurophilosophers, cognitive scientists and anyone interested in conscious perception and the mind-brain connection.